2018
DOI: 10.1039/c7ra12038a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of montmorillonite/hydrochar nanocomposites and application for 17β-estradiol and 17α-ethynylestradiol removal

Abstract: abWith a view to reducing estrogens pollution in aqueous environments, montmorillonite/hydrochar (MMT/ HC) with or without modification by KOH via hydrothermal carbonization process (HTC) were applied to remove 17b-estradiol (E2) and 17a-ethynylestradiol (EE2). The characterizations of MMT/HC indicated that MMT had been successfully attached onto HC surface, which could cause an improvement in the stability of the clay nanoparticles. MMT/HC with 1% KOH (MMT/HC-K1) exhibited excellent adsorption) compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The improved electron density of the benzene ring enables it to function as a powerful e − giver; at highly acidic pH (pH ≤ 2), the hydroxyl and ketonic functional groups are protonated, and the SE is in their cationic form. 92 The findings above corroborate the findings of other researchers who have equally accentuated that interactions occur between the phenolic moiety of SE and the e − acceptor groups tied to adsorbent, 95,104,105 and this results in efficacious adsorption.…”
Section: Adsorption Technique For the Removal Of Ses In Watersupporting
confidence: 89%
“…The improved electron density of the benzene ring enables it to function as a powerful e − giver; at highly acidic pH (pH ≤ 2), the hydroxyl and ketonic functional groups are protonated, and the SE is in their cationic form. 92 The findings above corroborate the findings of other researchers who have equally accentuated that interactions occur between the phenolic moiety of SE and the e − acceptor groups tied to adsorbent, 95,104,105 and this results in efficacious adsorption.…”
Section: Adsorption Technique For the Removal Of Ses In Watersupporting
confidence: 89%
“…The Freundlich model was the best interpretation of equilibrium sorption data of various EEs on BC [ 52 , 53 , 101 ], HC [ 52 , 58 ] and DG [ 12 ]. Differently, other works demonstrated that the Langmuir model was the most appropriate fit for EEs on BC [ 43 , 46 , 90 ] and HC [ 57 , 102 ].…”
Section: Sorptive Removal Of Estrogens By Biosorbentsmentioning
confidence: 98%
“…In order to enhance the adsorbing performance of HC, researchers have carried out several specific activation treatments during or after the HTC process [ 54 , 55 ]. Common activating agents adopted for HC are alkali metal hydroxides such as NaOH [ 56 ] and KOH [ 57 ] and single or binary salts [ 58 ].…”
Section: Biosorbents From Biowaste Recyclingmentioning
confidence: 99%
See 2 more Smart Citations